ARTICLES OF THE CLAIM MANUFACTURING IN CIVIL PROCEEDINGS - Грабовська, Ганна Миронівна; Жаб`як, Андріана Андріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article investigates the main innovations in the justice system that were introduced in the context of judicial reform. Methods of research: philosophical-ideological, general scientific and special methods were used in the work. Results: the main stories of the legal proceedings for civil justice were determined and the introduction of the information system of the judicial system was analyzed, as well as the problems and prospects of the implementation of the «Electronic Court» project in the system of legal proceedings of Ukraine were identified. Discussion: problems and Prospects for Introducing Innovations in the Justice System. The authors conclude that within the framework of the adopted narrative, for clarity and simplification of the trial, it is necessary to develop clear, transparent, understandable criteria for assigning one or another category of cases to insignificant ones and, accordingly, to consider these cases in the form of simplified lawsuits. This is important because the practical application of three fully updated procedural codes, including the Civil Procedural Code of Ukraine, has begun. Consequently, disputes regarding the feasibility of introducing certain innovations into domestic procedural codes are inferior to the analysis of the effectiveness of their implementation processes.